Laser Personalization and Digital Marketing on Gen Z Souvenir Purchase Intention - Santoso, Nuke Puji Lestari; Aini, Qurotul; Rahmadani, Rizki Galang; Wahid, Syahrul Mu'Arif (ADI Journal on Recent Innovation, 2025)
Optimizing digital business strategies for creative souvenir products using Mini Laser Packer technology aims to cater to the unique preferences of Gen Z. While previous studies have explored laser customization in traditional industries and digital marketing for Gen Z separately, a gap exists in understanding their spe- cific intersection within the creative souvenir sector. This paper addresses this gap by examining the adoption of Mini Laser Packer technology to meet Gen Z’s demand for personalized products through targeted digital marketing strate- gies, thus offering a novel perspective on value creation in this niche market. The research takes a quantitative approach, utilizing pre-test and post-test ex- perimental methods alongside regression analysis to evaluate changes in product quality and consumer response. Data were collected through surveys with Gen Z consumers, interviews with business owners, and direct observations. Find- ings show that the adoption of Mini Laser Packer significantly enhances product quality, particularly through more attractive, customizable designs that appeal to consumer preferences. Digital marketing strategies on social media and e- commerce platforms have proven effective in engaging Gen Z consumers with personalized offerings. Despite positive impacts, challenges remain, such as high technology investment costs and limitations in digital marketing utiliza- tion. Businesses are encouraged to leverage these insights to strengthen prod- uct competitiveness and deepen consumer relationships by offering personalized products on digital platforms favored by Gen Z.